Co-Overexpression of GRK5/ACTC1 Correlates With the Clinical Parameters and Poor Prognosis of Epithelial Ovarian Cancer - Liu, Longyang; Lv, Jin; Lin, Zhongqiu; Ning, Yingxia; Li, Jing; Liu, Ping; Chen, Chunlin (Frontiers in Molecular Biosciences, 2022)
BACKGROUND: The prognosis of epithelial ovarian cancer (EOC) is poor, and the present prognostic predictors of EOC are neither sensitive nor specific. OBJECTIVE: The aim of this study was to search the prognostic biomarkers of EOC, and to investigate the expression of G protein-coupled receptor kinase 5 (GRK5) and actin alpha cardiac muscle 1 (ACTC1) in EOC tissues (both paraffin-embedded and fresh-frozen tissues) and to explore their association with clinicopathological parameters and prognostic value in patients with EOC. METHODS: A total of 172 paraffin-embedded cancer tissues of EOC patients diagnosed and operated at the memorial hospital of Sun Yat-sen University between December 2009 and March 2017 and 41 paratumor tissues were collected and the expression of GRK5 and ACTC1 was examined using immunohistochemistry (IHC). Furthermore, 16 fresh-frozen EOC tissues and their matched paratumor tissues were collected from the Integrated Hospital of Traditional Chinese Medicine, Southern Medical University, between August 2013 and November 2019 and subjected to reverse-transcription quantitative PCR (RT-qPCR) analysis to detect the mRNA expression of GRK5 and ACTC1. RESULTS: The expression of GRK5 and ACTC1 was both higher in cancer tissues than in paratumor tissues. GRK5 expression was positively correlated with ACTC1 expression. In addition, GRK5, ACTC1 and GRK5/ACTC1 expression was associated with recurrence-free survival (RFS) and overall survival (OS) of EOC patients. Furthermore, multivariate logistic regression analysis indicated that GRK5+/ACTC1+ co-expression, intestinal metastasis, postoperative chemotherapy, platinum resistance and HIPEC were independent prognostic factors of EOC. CONCLUSIONS: GRK5 and ACTC1 are both upregulated in EOC compared with those in paratumor tissues. Co-expression of GRK5+/ACTC1+ rather than GRK5 or ACTC1 is an independent prognostic biomarker of EOC.